Currículo e identidade : um estudo de caso na Escola Agrícola Ministra Leonor Barreto Franco em Cristinápolis/SE - Jesus, Sandra Santos de (2017)
This research aimed to analyze the processes of identification made possible to the students of the Agricultural School Minister Leonor Barreto Franco, in the municipality of Cristinápolis – SE, by the curriculum developed. The context of the research is within the scope of Agricultural Teaching, specific to the Agricultural Technical course as an area that may or may not contribute to the development of processes of identification of the subjects of the field as a place of life. This research was developed in a qualitative, case-study approach. As research instruments, questionnaires, interviews and analysis of school documents were used. It was observed that the school develops a curriculum based on technical training, providing students with knowledge that allows them to operate in the perspective of sustainable agriculture. However, the eminently technical nature of the curricular proposal makes it difficult to train subjects committed to social and political practices related to the understanding of the field as a space for the production of life, not contemplate the diversity of elements that compose the Brazilian field. Identification in a perspective of the formation of a rural identity in the students was little evidenced. Therefore, it is understood that the curriculum in analysis reaffirms the presence of different perspectives between what is understood as Field Education and Agricultural Teaching, thus demarcating issues that are fundamental for the discussion about the historical training course of education in rural areas.